2021
DOI: 10.1128/msystems.00295-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of c-di-GMP/FleQ-Regulated New Target Genes, Including cyaA , Encoding Adenylate Cyclase, in Pseudomonas putida

Abstract: The bacterial second messenger cyclic diguanylate (c-di-GMP) modulates plankton-to-biofilm lifestyle transition of Pseudomonas species through its transcriptional regulatory effector FleQ. FleQ regulates transcription of biofilm- and flagellum-related genes in response to c-di-GMP. Through transcriptomic analysis and FleQ-DNA binding assay, this study identified five new target genes of c-di-GMP/FleQ in P. putida, including PP_0681, PP_0788, PP_4519 (lapE), PP_5222 (cyaA), and PP_5586. Except lapE encoding an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
(98 reference statements)
2
17
0
Order By: Relevance
“…putida compared to the wild-type strain. In agreement with this work, a significant number of those genes were related to cell motility and secretion processes, defence mechanisms, amino acid transport/metabolism, carbohydrate transport/metabolism, and signal transduction [68].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…putida compared to the wild-type strain. In agreement with this work, a significant number of those genes were related to cell motility and secretion processes, defence mechanisms, amino acid transport/metabolism, carbohydrate transport/metabolism, and signal transduction [68].…”
Section: Resultssupporting
confidence: 80%
“…aeruginosa with the finding of 89 activated genes and 249 repressed genes by this TF [4]. Regarding FleQ, Xiao et al (2021) [68] showed a similar number of up- and down-regulated genes, 172 and 272 respectively, in a fleQ mutant in P. putida compared to the wild-type strain.…”
Section: Resultsmentioning
confidence: 91%
“…Pseudomonas putida KT2440 could use K1-T6SS to eradicate a broad range of bacteria, including E. coli and some phytopathogens (Bernal et al, 2017). Previous studies and our recent transcriptome data suggested that c-di-GMP and FleQ regulated K1-T6SS transcription in P. putida (Wang et al, 2017a;Wang et al, 2017b;Xiao et al, 2021). However, the exact mechanism of FleQ-FleN-c-di-GMP complex regulating T6SS remains unclear.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies and our recent transcriptome data suggested that c‐di‐GMP and FleQ regulated K1‐T6SS transcription in P . putida (Wang et al ., 2017a; Wang et al ., 2017b; Xiao et al ., 2021). However, the exact mechanism of FleQ‐FleN‐c‐di‐GMP complex regulating T6SS remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…AAN69951), we found that tarR-tarS transcription was decreased in both wild-type strain with high-level c-di-GMP and fleQ deletion mutant (Xiao et al, 2021). We further compared tarR-tarS transcription in fleQ mutant and wild-type using qRT-PCR.…”
Section: C-di-gmp Inhibits Tarr-tars Transcription By Antagonizing Fleq Activationmentioning
confidence: 90%